Sintesis dan Karakterisasi Fotokatalis Hierarchical Porous TiO2/Cu (HPT/Cu) dengan Metode yang Ramah Lingkungan - Syawal, M Ichlas; Suryani, Okta (Departemen Kimia FMIPA UNP, 2024)
Most of the energy consumed comes from non-renewable fossil fuel resources. Therefore, renewable and environmentally friendly energy resources are needed, namely sunlight. One way to utilize sunlight is to store it into hydrogen compounds. Hydrogen comes from water through a process of breaking down its molecules which is called water decomposition. Water decomposition uses sunlight and a semiconductor photocatalyst, such as TiO2. In this research, TiO2 has been synthesized whose morphological structure has been modified (Hierarchical Porous TiO2) and doped with Cu metal to reduce the band gap. Hierarchical Porous TiO2 (HPT) has been successfully synthesized. XRD characterization to determine the structure and size of the particles. HPT has an anatase crystal structure with an average particle size of 19.24 nm. HPT has an energy band gap of 3.25 eV. Then doping with Cu metal causes the band gap to decrease to 2.79 eV. Metal doping has been proven to reduce the band gap energy of the HPT semiconductor photocatalyst